Impact of Workplace Bullying among Physicians of Tertiary Medical College Hospitals - Ata, Maliha; Rana, Mashud; Nourin, Nishat Anjum; Anik, Md Saidul Hoque; Ghosh, Ajay Kumar; Munna, Saifuddin; Barua, Happy Rani; Barua, Happy Rani; Hoque, Rozina (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Over the last decades , a range of studies evaluated that exposure to bullying and harassment among healthcare professionals while at work is associated with elevated level of stress symptoms both at work and everyday life. This phenomenon of abuse or belittlement is faced on a regular basis. The study aimed at evaluating prevalence and forms of physicians’bullying at their workplace with impact of stress among them. Materials and methods: This was a cross sectional questionnaire based study which was conducted among physicians who had been working for at least 6 months of two Medical College Hospitals. Results: 189 physicians provided data. Among them 131 (69.32%) experienced bullying at work place. It was found that female (52.67%) was bullied more than male (47.32%). The most common form of bullying was opinion and views ignored (71%). Depression (p=0.006) and feeling of stress (p= 000) were significantly associated with being bullied. There was significant association between harassment at work place faced by junior physicians (Intern and Postgraduate trainee) tantamount to take credit of work, persistent criticism, punishment task, intimidating use of discipline and the source of bullying. The source was mostly from professorial staff (40.38%) and trainee at higher level (36.54%). Conclusion: It is a dire need to raise awareness amongst health care professionals about the consequences of work place bullying and harassment. Without realization of harmful effect of bullying, it is not possible to provide a safe and sound workplace environment for collaborative as well as rewarding outcomes. JCMCTA 2023 ; 34 (1) : 25-30